2016
DOI: 10.1136/sextrans-2015-052048
|View full text |Cite
|
Sign up to set email alerts
|

Prediction ofChlamydia trachomatisinfection to facilitate selective screening on population and individual level: a cross-sectional study of a population-based screening programme

Abstract: A registry-based prediction model can facilitate selective Ct screening at population level, with further refinement at the individual level by including questionnaire risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Previous studies also found clustering of Ng within low SES regions and among migrant populations 9–11 16 18. Neighbourhood and regional SES had no influence on regional variance in Ct positivity, as is also described previously 19. However, regional degree of urbanisation was an important contributor to regional variance in Ct.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies also found clustering of Ng within low SES regions and among migrant populations 9–11 16 18. Neighbourhood and regional SES had no influence on regional variance in Ct positivity, as is also described previously 19. However, regional degree of urbanisation was an important contributor to regional variance in Ct.…”
Section: Discussionsupporting
confidence: 76%
“…For example, a recently developed prediction model to screen for Chlamydia trachomatis infection was developed in a dataset that was clustered within neighborhoods. 41 Given that the intended user of the model screens individuals from various neighborhoods, population-level performance measures were of interest.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Two types of prediction tools for binary outcomes can be distinguished: (1) a tool that can be used to predict an individual's probability of the presence of disease at the moment of prediction (i.e., a diagnostic prediction model) and (2) one that can be used to predict the probability of the future occurrence of an event (i.e., a prognostic prediction model). An example of the former is a model to estimate the probability of Chlamydia trachomatis infection to aid selective screening of youth at high risk of an infection [3]. An example of a prognostic prediction model to estimate an individual's probability of a future event is a model that estimates the probability of a successful vaginal birth after previous caesarean section, which is subsequently included in a decision aid to discuss the intended mode of delivery [4,5].…”
Section: Introductionmentioning
confidence: 99%